Professional Vision of Teachers and its Role in Developing the Characteristics of Inclusive Pedagogy During Sports Lessons in Middle Schools - Soran, Entethar Faroq Allyas (Jurusan Pendidikan Olah Raga dan Kepelatihan FKIP Universitas Jambi, 2025)
Physical education teachers are exposed to many challenges and problems during the implementation of lessons, which appear in several forms, including those related to the educational curriculum as well as the plans and methods they use in the teaching process. Hence, the research aims to reveal the level of possession of physical education teachers in middle schools with a professional vision in their field of work from their point of view. Also, to reveal the level of possession of physical education lessons of inclusive pedagogy characteristics from the teachers' point of view. The researcher used the descriptive approach using the survey and correlation methods in the research procedures. The researcher defined the research community as physical education teachers in schools affiliated with the Nineveh Education Directorate. The number of individuals in this sample is 293. The researcher reached a set of results: Physical education teachers in middle schools affiliated with the Nineveh Education Directorate have professional visions about their teaching job that are characterized by being average in level from their point of view. Physical education lessons in middle schools affiliated with the Nineveh Education Directorate are characterized by a low level of comprehensiveness in education from the point of view of physical education teachers. They concluded that the professional vision of physical education teachers plays an acceptable role in developing the characteristics of inclusive pedagogy for physical education lessons, with the two variables being linked by an excellent moral relationship.